Pengaruh Model Pembelajaran Pair Checks terhadap Kemampuan Menulis Teks Ulasan Siswa Kelas VIII SMPS Muhammadiyah 1 Medan - Rika Maharani; M. Joharis Lubis (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to (1) determine the ability of students of class VIII of SMPS Muhammadiyah 1 Medan in writing review texts without using the pair checks learning model, (2) determine the ability to write review texts in class VIII of SMPS Muhammadiyah 1 Medan using the pair checks learning model, (3) determine the effect of the pair checks learning model on the ability to write review texts in class VIII students of SMPS Muhammadiyah 1 Medan. This study involved all class VIII students totaling 351 students, with a sample of 69 people divided into two classes: a control class of 35 students and an experimental class of 34 students. This study used the quasi-experimental type of experimental method and the Posttest-Only Control Design research design. Data analysis techniques used such as analysis requirements test, normality test, and hypothesis test. The results of the study showed that the average ability to write review texts without using the pair checks learning model got a score of 69 which is included in the sufficient category. For the average value of the ability to write review texts using the pair checks learning model got a score of 81 which is included in the good category. Based on the results of the t-test that has been carried out, the results obtained show that the ability to write review texts using the pair checks learning model has a significant impact, as evidenced by the t-test value > t-table (7,772 > 1,996), indicating the influence of the pair checks learning model on the ability to write review texts in class VIII students of SMPS Muhammadiyah 1 Medan.